2006
DOI: 10.1051/0004-6361:20064873
|View full text |Cite
|
Sign up to set email alerts
|

Witnessing galaxy preprocessing in the local Universe: the case of a star-bursting group falling into Abell 1367

Abstract: We present a multiwavelength analysis of a compact group of galaxies infalling at high speed into the dynamically young cluster Abell 1367. Peculiar morphologies and unusually high Hα emission are associated with two giant galaxies and at least ten dwarfs/extragalactic HII regions, making this group the region with the highest density of star formation activity ever observed in the local clusters. Moreover Hα imaging observations reveal extraordinary complex trails of ionized gas behind the galaxies, with proj… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
160
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 170 publications
(175 citation statements)
references
References 90 publications
(150 reference statements)
12
160
3
Order By: Relevance
“…Indeed, dynamical friction and viscous processes at z 2 proceed on a timescale of <1 Gyr, which is at least one order of magnitude faster than in z ∼ 0 disc galaxies. In overdense environments, such as clusters, ram pressure may also play a role, demolishing the star-forming disc (Cortese et al 2006). Recently, Bundy et al (2010) demonstrated that the colour and morphological transformations should proceed through several separate stages and explored the strengths and weaknesses of several more sophisticated explanations, including environmental effects, internal stabilization, and disc regrowth by means of gas-rich mergers.…”
Section: Timescales For the Quenching Of The Star Formation And Morphmentioning
confidence: 99%
“…Indeed, dynamical friction and viscous processes at z 2 proceed on a timescale of <1 Gyr, which is at least one order of magnitude faster than in z ∼ 0 disc galaxies. In overdense environments, such as clusters, ram pressure may also play a role, demolishing the star-forming disc (Cortese et al 2006). Recently, Bundy et al (2010) demonstrated that the colour and morphological transformations should proceed through several separate stages and explored the strengths and weaknesses of several more sophisticated explanations, including environmental effects, internal stabilization, and disc regrowth by means of gas-rich mergers.…”
Section: Timescales For the Quenching Of The Star Formation And Morphmentioning
confidence: 99%
“…McGee et al 2009;Berrier et al 2009). Observational evidence has been found from the identification of groups embedded in the large-scale structure of clusters (Cortese et al 2006;Tanaka et al 2007;Ziparo et al 2012;Eckert et al 2014). This would explain, as already suggested by , the decreasing light contribution of the central brightest galaxies in clusters: BCGs would form in low-mass systems and then become bright galaxies in clusters as part of the hierarchical structure formation (Merritt 1985;Edge 1991;De Lucia & Blaizot 2007;De Lucia et al 2012).…”
Section: Richness and Bcg Contributionmentioning
confidence: 99%
“…In addition to atomic gas pulled from the parent galaxies, these collisional debris actually contain surprisingly large amounts of molecular gas formed in-situ (Braine et al 2000(Braine et al , 2001Lisenfeld et al 2002Lisenfeld et al , 2004Petitpas & Taylor 2005;Duc et al 2007). As the gas subsequently collapses, starforming regions are created with masses ranging from a few hundred solar masses, creating OB associations, the "emission line dots" (Gerhard et al 2002;Yoshida et al 2002;Sakai et al 2002;Weilbacher et al 2003;Ryan-Weber et al 2004;Mendes de Oliveira et al 2004;Cortese et al 2006;Werk et al 2008Werk et al , 2010 to objects as massive as dwarf galaxies named tidal dwarf galaxies (TDGs, Duc 1995;Duc & Mirabel 1998;Duc et al 2000Duc et al , 2007Hancock et al 2007Hancock et al , 2009). These objects, A&A 533, A19 (2011) even though formed from material once pertaining to their parent galaxies, have a radically different and simpler environment.…”
Section: Introductionmentioning
confidence: 99%